2016
DOI: 10.4314/thrb.v18i3.x
|View full text |Cite
|
Sign up to set email alerts
|

Trauma admissions among street children at a tertiary care hospital in north-western Tanzania: a neglected public health problem

Abstract: Background: Trauma among street children is an emerging but neglected public health problem in most low and middle income countries. This study was conducted to determine the incidence, etiological spectrum, injury characteristics and treatment outcome among street children and to identify the predictors of the outcome of these patients at Bugando Medical Centre in Mwanza, Tanzania.Methods: The study included street children aged <18 years. Routine investigations including haematological, biochemical and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Similarly, study findings in a descriptive prospective study involving street children under 18 years admitted for trauma at Bugando Medical Centre between 2008 and 2014 indicate that the mortality rate was 13.5 percent. The mortality was significantly associated with severe head injury [8]. Other studies with similar results include a prospective observational study carried out in Urban India to assess factors influencing mortality in the pre-hospital period after road traffic accidents also found that lack of personal protective gear was significantly associated with mortality.…”
Section: Use Of Personal Protective Devicementioning
confidence: 57%
“…Similarly, study findings in a descriptive prospective study involving street children under 18 years admitted for trauma at Bugando Medical Centre between 2008 and 2014 indicate that the mortality rate was 13.5 percent. The mortality was significantly associated with severe head injury [8]. Other studies with similar results include a prospective observational study carried out in Urban India to assess factors influencing mortality in the pre-hospital period after road traffic accidents also found that lack of personal protective gear was significantly associated with mortality.…”
Section: Use Of Personal Protective Devicementioning
confidence: 57%